Israel : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper analyzes the macro-fiscal implications of an increase in infrastructure spending, considering Israel's dual economy character. The efficiency of investment is key to ensuring growth benefits are achieved and to containing increases in the public debt ratio. Selecting projects with low rates of return, managing public investment inefficiently, or raising investment faster than absorptive capacity, can lead to weaker growth benefits and higher debt ratios that reduce the room to sustain increased public investment. Growth benefits will likely be insufficient to prevent a significant increase in debt ratios, indicating a need for revenue measures, where reductions in tax benefits are preferable. Allowing the public debt ratio to rise as much as 10 percentage points appears too high as Israel faces wider uncertainties than most advanced economies and it should also preserve fiscal space to facilitate structural reforms for long-term growth. Given Israel's very low civilian spending, the government should consider financing most of the additional investment with additional revenues. Israel's sizable foregone revenue from various tax benefits-around 5 percent of GDP per year-suggests significant scope for revenue gains. Our analysis also suggests that reducing tax benefits is least detrimental to growth, which in turn would be most positive for debt dynamics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet